The sport business handbook insights from 100+ leaders who shaped 50 years of the industry - Horrow, Richard B.
"Each of the 28 chapters tackles an essential topic that any person who wants to be a force in sport business will face early and often in his or her career. This revised edition includes new material added to the front and back matter, including a prologue, supplemental contribution pieces, and media perspective on the pandemic from a leading journalist"